Community Empowerment in Supporting Tourism in West Manggarai, Welak district, East Nusa Tenggara - Djatmiko, Achmad; Inarto, Agoes; Sari, Nurmita; Maulana, Ahmad; Khairunnisa, Qintara (KnE Social Sciences, 2025)
This research discusses the empowerment of rural communities in Welak District through tourism development. By using a qualitative approach and primary and secondary data collection methods, it focuses on community development as human resources. By understanding the concept of economic empowerment and implementing a village strategic plan, this research aims to increase community participation in developing the tourism sector. Interviews with government officials and local communities reveal challenges in maximizing tourism assets and prioritizing infrastructure development for tourism access. Overall, this research highlights the importance of community empowerment for sustainable tourism growth. The results show that the community around the tourist location had not been maximized in terms of utilizing tourism assets that could possibly become additional tourist destinations. Given the nature of the Labuan Bajo tourist destination, this was because there was still a “wait and see” attitude towards what they expected the government to be able to give them after they handed over the assets. On the other hand, the problem of infrastructure has not been a priority for access to tourist destinations.